Preparation method and process of CuO-Fe2O3 bimetallic oxide for high-selectivity preparation of 3-chloroaniline from 3-chloronitrobenzene

The CuO-Fe2O3 catalyst was prepared by Cu-Fe-MOF precursor, and the 3-chloronitrobenzene as 3-chloroaniline was catalyzed in ethanol solvents at room temperature and pressure, which solved the low selectivity of existing catalysts and harsh reaction conditions. The problem of this problem has achieved efficient and environmentally friendly preparation of 3-chloroaniline, which has the potential for industrial application.

CN119158572APending Publication Date: 2024-12-20INNER MONGOLIA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410724893.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-05
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing catalysts have problems such as low selectivity, harsh reaction conditions, environmental pollution and equipment corrosion in the hydrogenation reaction of 3-chloronitrobenzene. The precious metal catalysts are costly and not environmentally friendly, making it difficult to achieve efficient and economical 3- Preparation of chloroaniline.

Method used

Cu-Fe-MOF as a precursor was used to prepare CuO-Fe2O3 bimetallic catalyst, and 3-chloronitrobenzene as 3-chloroaniline was catalyzed in ethanol solvents with a simple one-step calcination method at room temperature and pressure, using MOF Precise control of nanostructures and compositions enables efficient catalysis.

Benefits of technology

It has achieved efficient and environmentally friendly catalyzing of 3-chloronitrobenzene as 3-chloroaniline under mild conditions. The catalyst has high chemical selectivity, stability and low cost, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention belongs to the field of synthesis of chloroaniline compounds, and particularly relates to preparation of a high-selectivity catalyst CuO-Fe2O3 and application of the high-selectivity catalyst CuO-Fe2O3 in a catalytic reduction technical method for preparing 3-chloroaniline through selective reduction of 3-chloronitrobenzene. According to the invention, MOFs with double metal centers are prepared by using a simple synthesis method, and the MOFs are further used as a reaction precursor to prepare the CuO-Fe2O3 composite catalyst. Under normal temperature and normal pressure, the prepared CuO-Fe2O3 composite catalyst can completely hydrogenate 3-chloronitrobenzene into 3-chloroaniline within 7 min in the reaction of selectively reducing 3-chloronitrobenzene into 3-chloroaniline, and the conversion rate and selectivity are kept stable in five times of circulation processes. The reaction system is normal in temperature and pressure, the reaction solvent is non-toxic and harmless, the catalyst is low in cost and free of pollution, the catalytic hydrogenation rate is high, impurities are avoided, and the purity of chloroaniline target products is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation method and process of a catalyst for preparing 3-chloroaniline by highly selective catalytic hydrogenation of 3-chloronitrobenzene, and specifically to a unique preparation process of a CuO-Fe2O3 catalyst using MOF as a precursor, wherein the catalyst is used for highly selectively catalyzing 3-chloronitrobenzene to prepare 3-chloroaniline in a clean and green ethanol solvent at room temperature and pressure. Background Art

[0002] Chloroaniline compounds are an important class of industrial intermediates used to produce a variety of specific fine chemicals, including drugs, organic dyes, herbicides and pesticides. Among them, 3-chloroaniline can be synthesized by selective hydrogenation using a transition metal catalyst. Since the reduction of the nitro group and the hydrogenolysis of the C-Cl bond are competing reactions, it is difficult to completely avoid the unwanted hydrogenolysis of the C-Cl bond during the catalytic hydrogenation process. During the reaction, when the hydrogenolysis of the C-Cl bond occurs, hydrochloric acid and aniline are generated, which reduces the yield and the generated acid will also corrode the equipment and increase the difficulty of product separation. Therefore, the economic benefits of the preparation of chloroaniline compounds depend on the catalyst performance and reaction process.

[0003] The hydrogenation reduction reaction conditions of chloronitrobenzene are relatively harsh, generally requiring completion at >323K, >1.0 MPa and >20 min. In addition, organic solvents are used as reaction media in these hydrogenation reactions, which can lead to environmental pollution and high energy consumption in the subsequent separation of the reaction mixture, all of which limit their practical applications. Therefore, it is of great economic and scientific significance to develop specific catalysts with ideal selectivity to enable chloronitrobenzene to be efficiently reduced to synthesize chloroaniline under mild reaction conditions and green solvents.

[0004] A large number of traditional catalysts based on precious metals are widely used in the selective hydrogenation reaction of chloronitrobenzene. However, due to the high cost of precious metals, large metal loading, easy aggregation of nanoparticles, harsh reaction conditions and short catalytic cycle, their application range is narrow and environmental and safety issues are prominent. Therefore, from the perspective of economic and sustainable development, it is very important to prepare a non-precious metal-based catalyst that is easy to use, highly safe and environmentally friendly.

[0005] Non-precious metal oxides (especially copper and iron) are promising catalysts due to their sustainability, large supply, environmental friendliness and low toxicity. Traditional oxide preparation is generally carried out by thermal decomposition, water / solvothermal and coprecipitation methods, but the above methods have the disadvantages of high equipment investment, high energy consumption, easy product agglomeration and the generation of toxic gases. The preparation of oxide catalysts using metal organic framework (MOFs) nanoparticles as precursors can precisely control their composition, pore size and shape by changing the type of metal ions and the structure of organic ligands, thereby obtaining the desired oxide nanostructure and morphology. During the synthesis process, MOFs can stably maintain their structure and can be uniformly converted into the corresponding oxides under appropriate heat treatment conditions, which is conducive to obtaining oxide nanoparticles with high crystallinity and good dispersion. In addition, some MOFs materials can be decomposed into oxides at relatively low temperatures, which helps to reduce energy consumption and avoid phase change and structural damage during high temperature processes. Therefore, compared with the traditional solid-phase or solution methods for preparing oxides, the method using MOFs precursors is usually simpler, more efficient and more suitable for industrial production and application.

[0006] This patent designs a CuO-Fe2O3 composite catalyst prepared with Cu-Fe-MOF as a precursor. It can prepare 3-chloroaniline through a liquid phase reduction reaction with 3-chloronitrobenzene as the initial raw material under green and environmentally friendly reaction conditions. It has fast reaction, high chemical selectivity and high yield. Summary of the invention

[0007] The present invention aims to provide a method for preparing a CuO-Fe2O3 bimetallic catalyst for selective reduction of 3-chloronitrobenzene to prepare 3-chloroaniline under economical, environmentally friendly and safe operating conditions, which specifically comprises the following steps: Step 1. Preparation of Cu-Fe-MOF Prepare a dispersion alkali solution A with a molar concentration of sodium hydroxide and trimesic acid of 1:38, then dissolve ferric sulfate and copper nitrate in secondary water to obtain a dispersion solution B with a central metal atom; slowly add the dispersion solution B to the dispersion solution A, and stir at room temperature until the reaction is complete; after the reaction is completed, collect the product by centrifugation, wash, and dry to obtain Cu-Fe-MOF, which is used as a precursor material for preparing CuO-Fe2O3; Step 2, Preparation of CuO-Fe2O3 The Cu-Fe-MOF is calcined in air, and the MOF structure is gradually induced to collapse, and the MOF structure is gradually transformed into a bimetallic oxide. After the calcination is completed, the product is taken out and ground into powder, so that a CuO-Fe2O3 bimetallic oxide catalyst with a specific catalytic function is obtained, which is stored for later use; In step 1, the concentrations of sodium hydroxide and trimesic acid in the dispersed alkali solution A are 0.1 mol / L and 0.38 mol / L, respectively.

[0008] In step 1, the stirring time at room temperature is 12 to 24 h.

[0009] In step 1, the concentration of ferric sulfate is 0.02 mol / L, the molar ratio of Fe to Cu is 1:n (n=0-3), and the volume ratio of dispersion A to dispersion B is 7:13.

[0010] In step 1, the drying temperature is 50-60°C and the drying time is 5-10 h.

[0011] In step 2, the calcination method is to maintain a constant temperature at 350-500°C for 100-300 min, and the calcination heating rate is 4-7°C / min.

[0012] Performance evaluation of the prepared catalyst in catalyzing the preparation of 3-chloroaniline from 3-chloronitrobenzene Take 14 µL of 3-chloronitrobenzene and add it to the reaction tube. Then add 5 mg of the prepared catalyst and 6 mL of anhydrous ethanol. Ultrasonic dispersion is performed. Then nitrogen is introduced into the solution to remove oxygen. Then, 2 mL of 0.15 mol·L -1 The reaction was initiated by NH3BH3. After the reaction, 6 μL of o-xylene was added as an internal standard, and the product was analyzed by gas chromatograph with a flame ionization detector.

[0013] The beneficial effects of the present invention are: (1) The present invention uses a simple synthesis method and MOFs as reaction precursors to obtain a CuO-Fe2O3 composite catalyst with a bimetallic center, high crystallinity and good dispersion.

[0014] (2) The catalyst preparation process of the present invention is simple to operate, highly efficient, does not require complex equipment, and the raw materials used are non-toxic and low-cost. The catalyst has the potential for large-scale preparation and industrial application.

[0015] (3) The CuO-Fe2O3 composite catalyst prepared by the present invention using a simple one-step calcination method can efficiently complete the highly selective reduction of 3-chloronitrobenzene to 3-chlorobenzeneamine in an environmentally friendly solvent at room temperature and pressure. It has high catalytic activity, short reaction time, and stable reaction products. It is expected to further promote the process upgrade of large-scale preparation of 3-chlorobenzeneamine under mild conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 (a) is the X-ray powder diffraction pattern of MOF precursor, Figure 1 (b) is the X-ray powder diffraction pattern of the sample after calcination in air; Figure 1(c) and (d) are the XRD patterns of the prepared control samples Cu3Zn1O, Cu3Ni1O, Cu3Co1O and Cu3In1O, demonstrating the successful preparation of the four bimetallic oxides.

[0017] Figure 2 The SEM images of the prepared samples are (a) Cu-MOF, (b) Fe-MOF, (c) Cu3Fe1-MOF, (d, e) Cu2O / CuO, and (f, g) Cu3Fe1O. The scanning results show that Cu-MOF is a nanosheet with a smooth surface, about 1-3 μm in length and about 400-600 nm in width; Fe-MOF is a polyhedral structure with some small nanoparticles attached, and the bimetallic Cu3Fe1-MOF presents a nanorod structure with a length of about 250 nm and uniform size. The Cu2O / CuO crystals obtained by calcining Cu-MOF aggregate to form large blocks with a rough surface and a honeycomb structure; the structure of Cu3Fe1-MOF after calcining to obtain Cu3Fe1O is also destroyed, forming irregular nanoparticles.

[0018] Figure 3 X-ray photoelectron spectra of the prepared samples, (a) is the total spectrum, (b) is the 2p orbital of Cu, and (c) is the 2p orbital of Fe.

[0019] Figure 4 are the specific surface area and pore diameter of the prepared samples, where the specific surface areas of Cu2O / CuO and Fe2O3 are 1.187 m 2 g -1 and 44.351 m 2 g -1 The specific surface area of ​​Cu3Fe1O is 22.017 m 2 g -1 This is mainly due to the close contact and recombination of Fe2O3 and copper oxide, which makes part of the Fe2O3 pore size covered, further proving the successful recombination of the two components.

[0020] Figure 5 a is the selectivity and conversion rate of the prepared catalyst for reducing 3-nitrochlorobenzene; when Cu2O / CuO and Fe2O3 are used as catalysts, the reduction product of 3-chloronitrobenzene is 3-chloroaniline, but the conversion rate is low. After the two are combined, Cu3Fe1O shows the highest conversion rate and selectivity (100%) for generating 3-chloroaniline; Figure 5 b is the activity test of Cu3Fe1O catalyst at different reaction times. The results show that the target product 3-chloroaniline can be completely converted in 7 min.

[0021] Figure 6The cyclic stability of Cu3Fe1O on 3-chloronitrobenzene was studied. The results showed that after five cycles, the reaction selectivity and conversion rate still showed no downward trend, indicating that the catalyst can be recycled and reused many times and has excellent cyclic stability.

[0022] Figure 7 In situ infrared spectrum (DRTFTS) of 3-chloroaniline prepared from 3-chloronitrobenzene as the starting material and Cu3Fe1O as the catalyst. First, the nitro group is adsorbed on the catalyst surface. As the reaction time increases, the characteristic peak of the nitro group gradually weakens and increases to 1485 cm -1 and 1463 cm -1 New peaks belonging to σ(NO) and σ(NOH) appeared at 3392 cm -1 and 1624 cm -1 A new peak also appeared at , which corresponds to the characteristic peak of σ(NH) of the target product. In addition, no peak attributed to N=N was detected during the reaction, indicating that no biphenyl was generated during the reaction, which is consistent with the gas chromatography results. These results indicate that the catalytic hydrogenation of 3-chloronitrobenzene on the Cu3Fe1O surface follows a direct pathway. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with specific embodiments. Example 1

[0024] Preparation of Cu2O / CuO: 0.53 g NaOH was dissolved in 35 mL water, and then 0.735 g trimesic acid was added and stirred until completely dispersed, which was recorded as solution A; 0.9777 g Cu(NO3)2·3H2O was added to 65 mL water and stirred until completely dissolved, which was recorded as solution B. Under stirring, solution B was slowly added dropwise to solution A, and then stirred at room temperature for 15 h until the reaction was complete; after the reaction was completed, the product was collected by centrifugation, washed with deionized water and ethanol, and dried in a 60 ℃ oven to obtain CuO / MOF; then 0.2 g CuO / MOF was taken and placed in a porcelain boat, and kept at 400 ℃ in an air atmosphere for 2 h at a heating rate of 5 ℃ / min in a tube furnace to obtain Cu2O / CuO, which was used as a control material for the composite catalytic material.

[0025] Cu2O / CuO catalytic hydrogenation performance test: Take 14 µL of 3-chloronitrobenzene and add it to the reaction tube. Then add 5 mg of Cu2O / CuO and 6 mL of anhydrous ethanol. Ultrasonic dispersion is performed. Then nitrogen is introduced into the solution to remove oxygen. Then, 2 mL of 0.15 mol·L-1 The reaction was initiated by NH3BH3. After the reaction was completed, 6 μL of o-xylene was added as an internal standard and the product was analyzed by a gas chromatograph with a flame ionization detector. The conversion rate of 3-chloronitrobenzene was 28%, and the selectivity for generating 3-chlorobenzene ammonia was 100%. Example 2

[0026] Preparation of Fe2O3: Dissolve 0.53 g NaOH in 35 mL water, add 0.735 g trimesic acid, stir until completely dispersed, and record it as solution A. Add 0.375 g FeSO4·7H2O to 65 mL water, stir until completely dissolved, and record it as solution B; under stirring, slowly add solution B dropwise to solution A, and then stir at room temperature for 15 h until the reaction is complete. After the reaction is completed, the product is collected by centrifugation, washed with deionized water and ethanol, and dried in a 60 ℃ oven to obtain Fe-MOF. Then take 0.2 g Fe-MOF and put it into a porcelain boat. In a tube furnace, keep it at 400 ℃ in an air atmosphere for 2 h at a heating rate of 5 ℃ / min to obtain Fe2O3.

[0027] Fe2O3 catalytic hydrogenation performance test: Take 14 µL of 3-chloronitrobenzene and add it to the reaction tube. Then add 5 mg of Fe2O3 and 6 mL of anhydrous ethanol and disperse it by ultrasonic. Then, nitrogen gas is passed into the solution to remove oxygen. Then, 2 mL of 0.15 mol·L -1 The reaction was initiated by NH3BH3. After the reaction was completed, 6 μL of o-xylene was added as an internal standard and the product was analyzed by a gas chromatograph with a flame ionization detector. The conversion rate of 3-chloronitrobenzene was 28%, and the selectivity for generating 3-chlorobenzene ammonia was 100%. Example 3

[0028] 0.53 g NaOH was dissolved in 35 mL water, and then 0.735 g trimesic acid was added and stirred until completely dispersed, which was recorded as solution A. 0.375 g FeSO4·7H2O and 0.326 g Cu(NO3)2·3H2O were added to 65 mL water and stirred until completely dissolved, which was recorded as solution B. Under stirring, solution B was slowly added dropwise to solution A, and then stirred at room temperature for 15 h until the reaction was complete; after the reaction was completed, the product was collected by centrifugation, washed with deionized water and ethanol, and dried in a 60°C oven to obtain Cu1Fe1-MOF; then 0.2 g Cu1Fe1-MOF was taken and placed in a porcelain boat, and kept at 400°C in an air atmosphere for 2 h at a heating rate of 5°C / min in a tube furnace to obtain Cu1Fe1O.

[0029] Cu1Fe1O catalytic hydrogenation performance test: Take 14 µL of 3-chloronitrobenzene and add it to the reaction tube. Then add 5 mg of Cu1Fe1O and 6 mL of anhydrous ethanol and disperse by ultrasonic. Then, nitrogen is passed into the solution to remove oxygen. Then, 2 mL of 0.15 mol·L -1 The reaction was initiated by NH3BH3. After the reaction was completed, 6 μL of o-xylene was added as an internal standard and the product was analyzed by a gas chromatograph with a flame ionization detector. The conversion rate of 3-chloronitrobenzene was 56%, and the selectivity for generating 3-chlorobenzene ammonia was 100%. Example 4

[0030] 0.53 g NaOH was dissolved in 35 mL water, and then 0.735 g trimesic acid was added and stirred until completely dispersed, which was recorded as solution A; 1.123 g FeSO4·7H2O and 0.326 g Cu(NO3)2·3H2O were added to 65 mL water and stirred until completely dissolved, which was recorded as solution B; under stirring, solution B was slowly added dropwise to solution A, and then stirred at room temperature for 15 h; finally, the product was collected by centrifugation, washed with deionized water and ethanol, and dried in a 60 ℃ oven to obtain Cu3Fe1-MOF. Then 0.2 g Cu1Fe3-MOF was taken and placed in a porcelain boat, and kept at 400 ℃ in an air atmosphere for 2 h at a heating rate of 5 ℃ / min in a tube furnace to obtain Cu1Fe3O.

[0031] Cu1Fe3O catalytic hydrogenation performance test: Take 14 µL of 3-chloronitrobenzene and add it to the reaction tube. Then add 5 mg of Cu1Fe3O and 6 mL of anhydrous ethanol and disperse by ultrasonic. Then, nitrogen is introduced into the solution to remove oxygen. Then, 2 mL of 0.15 mol·L -1 The reaction was initiated by NH3BH3. After the reaction was completed, 6 μL of o-xylene was added as an internal standard and the product was analyzed by a gas chromatograph with a flame ionization detector. The conversion rate of 3-chloronitrobenzene was 100%, and the selectivity for generating 3-chlorobenzene ammonia was 100%. Example 5

[0032] 0.53 g NaOH was dissolved in 35 mL water, and then 0.735 g trimesic acid was added and stirred until completely dispersed, which was recorded as solution A. 0.375 g FeSO4·7H2O and 0.978 g Cu(NO3)2·3H2O were added to 65 mL water and stirred until completely dissolved, which was recorded as solution B. Under stirring, solution B was slowly added dropwise to solution A, and then stirred at room temperature for 15 h. Finally, the product was collected by centrifugation, washed with deionized water and ethanol, and dried in a 60 °C oven to obtain Cu3Fe1-MOF. Then 0.2 g Cu3Fe1-MOF was taken and placed in a porcelain boat. In a tube furnace, the temperature was increased at a rate of 5 °C / min and maintained at 400 °C in an air atmosphere for 2 h to obtain Cu3Fe1O.

[0033] Cu3Fe1O catalytic hydrogenation performance test: Take 14 µL of 3-nitrochlorobenzene and add it to the reaction tube. Then add 5 mg of Cu3Fe1O and 6 mL of anhydrous ethanol and disperse by ultrasonic. Then, nitrogen is introduced into the solution to remove oxygen. Then, 2 mL of 0.15 mol·L -1 The reaction was initiated by NH3BH3. After the reaction was completed, 6 μL of o-xylene was added as an internal standard and the product was analyzed by a gas chromatograph with a flame ionization detector. The conversion rate of 3-nitrochlorobenzene was 22%, and the selectivity for generating 3-chlorobenzene ammonia was 100%.

Claims

1. A method and process for preparing CuO-Fe2O3 bimetallic oxide for high selectivity preparation of 3-chloroaniline from 3-chloronitrobenzene, characterized in that: Follow the steps below: Step 1. Preparation of Cu-Fe-MOF Prepare a dispersion alkali solution A with a molar ratio of trimesic acid to sodium hydroxide of 1:38, then dissolve iron sulfate and copper nitrate in secondary water to obtain a dispersion B with a central metal atom; slowly add dispersion B to dispersion A, and stir at room temperature for 12-24 h until the reaction is complete; the concentrations of sodium hydroxide and trimesic acid in the dispersion alkali solution A are 0.1 mol / L and 0.38 mol / L, respectively, the concentration of iron sulfate is 0.02 mol / L, the molar ratio of Fe to Cu is 1:n (n=0-3), and the volume ratio of dispersion A to B is 7:

13. After the reaction is completed, the product is collected by centrifugation, washed, and dried to obtain Cu-Fe-MOF; Step 2, Preparation of CuO-Fe2O3 The Cu-Fe-MOF is calcined in an air atmosphere, and the MOF structure is gradually induced to collapse, gradually transitioning to a bimetallic oxide. After the calcination is completed, the product is taken out and ground into powder to obtain a CuO-Fe2O3 bimetallic oxide catalyst with a specific catalytic function, which is stored for later use.

2. The use of the CuO-Fe2O3 bimetallic oxide catalyst prepared by the preparation method according to claim 1 in the catalytic reaction of preparing 3-chloroaniline from 3-chloronitrobenzene, characterized in that: 14 µL of 3-chloronitrobenzene was added to the reaction tube, followed by 5 mg of the prepared catalyst and 6 mL of anhydrous ethanol. The mixture was dispersed by ultrasonication, and nitrogen was introduced into the solution to remove oxygen. Subsequently, 2 mL of 0.15 mol·L -1 The reaction was initiated by NH3BH3. After the reaction, 6 μL of o-xylene was added as an internal standard, and the product was analyzed by gas chromatograph with a flame ionization detector.

3. The method for preparing the catalyst according to claim 1, characterized in that: The Cu-Fe-MOF prepared in step 1 is used as a precursor and calcined in an air atmosphere to prepare a CuO-Fe2O3 bimetallic oxide catalyst.

4. The use of the CuO-Fe2O3 bimetallic oxide catalyst according to claim 2 in the reaction of catalyzing 3-chloronitrobenzene to prepare 3-chloroaniline, characterized in that: NH3BH3 is a reducing agent.

5. The use of the CuO-Fe2O3 bimetallic oxide catalyst according to claim 2 in the reaction of catalyzing 3-chloronitrobenzene to prepare 3-chloroaniline, characterized in that: Using the prepared Cu3Fe1O catalyst, 3-chloronitrobenzene can be completely converted into 3-chloroaniline by catalytic reduction at room temperature and pressure.

6. Use of the CuO-Fe2O3 composite photocatalyst prepared according to the preparation method according to any one of claims 1 to 5 for highly selective reduction of 3-chloronitrobenzene to 3-chloroaniline at room temperature and pressure.